Role Model Attributes as Correlates of Slow Learners’ Motivation and Understanding of Chemistry Concepts in Lagos State Schools - Okafor, Ngozi (NIU Journal of Humanities, 2022)
The purpose of the study was to investigate the influence of role model attributes (creativity; confidence and moral) and school locations (urban and peri-urban) on slow learners motivation and understanding of chemistry concept in Lagos State secondary schools of Nigeria. Slow learners considered were Senior Secondary School Three (SSS3) chemistry students that scored 20% and below in the urban and peri-urban locations during the 2019 Mock Examinations. Five null hypotheses guided the study. It was an ex-post facto research design involving 180 urban and peri-urban Senior Secondary School three chemistry slow learners in two Districts of Lagos State, Nigeria. Chemistry Understanding Test (CUT); Role Model Attributes Scale (RMAS) and Slow Learners Motivational Scale (SLMS) were the three instruments used in data collection. Data were analyzed using mean, standard deviation, Pearson correlation coefficient, regression analysis and independent t-test. The results show a strong positive influence of role model creativity; a weak positive influence of role model confidence and a non-significant influence role model moral attributes respectively on slow learners motivation and understanding of chemistry concept. There was a significant combined influence of role model creativity, moral and confidence but a non-significant influence of urban and peri urban locations on secondary school slow learners’ motivation and understanding of chemistry concept. The paper concludes that role models should serve as confidant, counselor and objective adviser for performance improvement of secondary school slow learners in chemistry and recommends that school administrators, teachers and parents in both urban and peri-urban locations should be students’ role models by setting high moral standard, self-confidence, positive attitude and values for their successful accomplishment in secondary school chemistry learning outcomes. Keywords: Creativity, Confidence, Moral, Urban, Peri-Urban